2021
DOI: 10.21203/rs.3.rs-1083275/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Pelvic Floor Muscle Training on Pelvic Floor Function and Sexuality Postpartum. A Randomized Study Including 300 Primiparous

Abstract: PurposeAlthough pregnancy and childbirth are physiological processes, they may be associated with pelvic floor disorders. The aim of this study was to evaluate the influence of pelvic floor muscle training on postpartum pelvic floor and sexual function of primiparous. MethodsThis is a randomized, prospective study including 300 primiparous women. Inclusion criteria were the delivery of the first, mature baby, the ability to speak, understand German. The participants were evaluated by clinical examinations and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The same two studies assessed the VRP, and one found a significant VRP increase in the PFMT group [30]. Indeed, several studies with women of the general population demonstrated an increase of the PFM maximal strength after PFMT [32][33][34]. It is known that a strong pelvic floor positioned at an optimal level within the pelvis can be a crucial factor in counteracting the increases in IAP that occur during high-impact activities [13].…”
Section: Generalmentioning
confidence: 99%
“…The same two studies assessed the VRP, and one found a significant VRP increase in the PFMT group [30]. Indeed, several studies with women of the general population demonstrated an increase of the PFM maximal strength after PFMT [32][33][34]. It is known that a strong pelvic floor positioned at an optimal level within the pelvis can be a crucial factor in counteracting the increases in IAP that occur during high-impact activities [13].…”
Section: Generalmentioning
confidence: 99%